The Impact of Investment Decisions on Firm Profitability of Non-Financial Sectors in Pakistan: Mediating Role of Sales Growth - Abbas, Qaiser; Ahmad, Riaz; Asif, Muhammed; Mehmood, Abid (iRASD Journal of Economics, 2022)
Investment decisions within the organizations are critical for firm’s profitability and also have a long-term impact because many of these decisions are irreversible. Firms with limited funds can achieve impressive returns if their investments are well-planned. Therefore, the research objective is to determine the impact of investment decisions on firm profitability (earning per share) of non-financial sector (Communication, media industry, energy sector etc.) of Pakistan. For this purpose, data was collected for the period of 2011-2021 from the annual reports of non-financial companies which were listed in 100 index Pakistan Stock exchange. The quantitative research approach, longitudinal research design and panel data approach has been used in the study. The panel data results indicates that working capital management (WCM) indicators namely inventory turnover ratio (ITO), average collection period (ACP), average payment period (APP) and cash conversions cycle (CCC) have positive and significant effect on earnings per share. In the same vein, capital expenditure also have positive and significant effect on earnings per share and also has indirect effect through the mediating effect of sales growth which indicates partial mediation because the coefficient after mediation was lower as compared to the direct effect. Based on the findings, the research has contributed a body of literature in the extant literature along with the significant and mediating effect. Therefore, this study could be considered to be a pioneer study that could help the researchers to conduct their research in future. This study could also help to the managers and decisions makers to know about the importance of investment decisions to increase firm profitability.